Changes on Recycling Behaviors Based on Governmental Programs (Study Case in Bendungan Village, Indonesia) - Dafi Dinansyah Wiradimadja; Hisatsuna Mori; Riza Rizkiah (Sainteks: Jurnal Sain dan Teknik, 2023)
Environmental problems such as erosion, flooding, are mainly caused by human activities itself. Due to main environmental problems mainly came or originated from man, the solutions or prevention effort to repair the environment, must involve human factors in its planning. In Indonesia in general, including in Bendungan Village, limited insight, lack of skills, poor health, and a low work ethic are all internal factors that cause environmental problems. Furthermore, the lack of knowledge about the environment is one of the causes of the emergence of environmentally destructive behavior that is carried out unconsciously. One of the problems in this village is garbage, people throw garbage into drains and empty land because they are not aware of the consequences of their actions. One solution that exists to solve environmental problems by involving human factors in it is through capacity building, one of which is through a sustainability education and incentive given by the West java Government. Through this concept, citizens are given education about the impact of their previous behavior, one of them is the behavior of littering. The program also provides economic value to waste so that there is an incentive to maintain the condition or waste managing waste in their village. This research used Mixed Methods approach (quantitative and qualitative) and use secondary data review, direct observation and semi semi-structured interviewing to collect the data. This research found that the main factor for the success of this program is the people who willing to be open concerning the program and its concepts, thus becoming aware about their environmental problems, they willing to work for the benefit of their village. In this village the push factor are economic and re-education aspects that move the people to save their environment. The economic benefit from garbage bank also have helped this program. The obstacles to the program in this village are the lack of facilities that they have, and for cadres to teach people about the environment, the lack of the government to provide formal education for the people and the last obstacle of this program is the economic factor, low amount of sellable garbage such as PET and cans have become major obstacle in promoting garbage bank.